Impact of evaluation method shifts on student performance: an analysis of irregular improvement in passing percentages during COVID-19 at an Ecuadorian institution - Esteban Guevara Hidalgo (International Journal for Educational Integrity)
Abstract The COVID-19 pandemic had a profound impact on education, forcing many teachers and students who were not used to online education to adapt to an unanticipated reality by improvising new teaching and learning methods. Within the realm of virtual education, the evaluation methods underwent a transformation, with some assessments shifting towards multiple-choice tests while others attempted to replicate traditional pen-and-paper exams. This study conducts a comparative analysis of these two types of evaluations, utilizing real data from a virtual semester during the COVID-19 pandemic at an Ecuadorian institution. It aims to assess the impact of transitioning from one evaluation method to the other, revealing fundamental structural differences. These differences can lead to disparities that unfairly advantage or disadvantage certain student groups based on the evaluation method used. Beyond identifying the causes of these discrepancies, the study reveals that, for the specific case and dataset analyzed, the shift to virtual education led to a significant and abrupt increase in passing percentages. Moreover, under one specific type of evaluation, there is a possibility that a minimum of 21.1% of students may have passed a course due to cheating or other forms of academic dishonesty, while at least 5.5% could have failed that course despite possessing the necessary capabilities.